The Gendered and Occupational Status Nature of Workplace Bullying - M., Fapohunda, Tinuke. (American Journal of Social Sciences and Humanities, 2019)
The study explored gender and occupational status dissimilarities in the experience of workplace bullying. Data from 327 workers in four different ministries in the Lagos State Public Service in Nigeria was gathered through a questionnaire. The MDM Questionnaire developed by Merecz-Kot and Cębrzyńska (2008) was adopted. The value of Cronbachα coefficient was 0.876. The Chi-Square Test and the two-way Analysis of Variance (ANOVA) were employed for analyses. Altogether, the results exemplify gender disparities both in the occurrence, rates and types of workplace bullying, and also that gender is vital in how targets and third parties understand and react to bullying. 70% of the female respondents as opposed to 49% of the male respondents reported having experienced bullying at work. This disparity was statistically significant. Again, 56% of the female victims reported being bullied by another female in the workplace while 41% were bullied by a male. For 60% of the female victims, their bullies were individuals with authority over them like managers and supervisors. While 20% were identified as co-workers of higher rankings, 16% were bullied by co-workers of the same ranking, and 4% were bullied by co-workers of lower rankings. The results substantiate the central position of gender disparities in predicting workplace bullying and sustain the outlook that gender is not simply a personal precursor of bullying, but instead serves as a social feature that manipulates the occurrence of workplace bullying. Since most victims are women, bullying becomes an instrument for sustaining gender inequality.